Eye-tracking consumers' awareness of beef brands. Issue 2 (2nd April 2020) - Lombard, W. A.; Van Zyl, J. H.; Beelders, T. R.
ABSTRACT: Beef consumers now have the power in the market. Consumers are extensively exposed to advertisements, but the human brain can only process a limited amount of this information. Thus, products must be differentiated in order to stand out in the market place. Branding provides one manner in which products can be differentiated. This study investigated red meat consumers' attention towards beef brand labelling in the Mangaung Metropolitan Municipality. A complete dataset for 307 respondents was extracted and used to generate the results for this study. Results showed that 30.6% of the participants preferred to purchase their beef from a certain brand. Correlation results showed that higher educated, younger and consumers from higher income groups were more likely to pay attention to a less familiar beef brand. Consumers in higher income groups, however, took longer before paying attention to the brand label for the first time. No significant correlation was found for a more familiar beef brand. When new beef brands plan to enter a market, they should identify a market that has a large number of young, highly educated consumers who earn higher incomes, since they are more likely to pay attention to an unfamiliar beef brand.